2017
DOI: 10.1080/10428194.2017.1307981
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIb expression in early stage chronic lymphocytic leukemia

Abstract: In normal B-cells, B-cell antigen receptor (BCR) signaling can be negatively regulated by the low-affinity receptor FcγRIIb (CD32b). To better understand the role of FcγRIIb in chronic lymphocytic leukemia (CLL), we correlated its expression on 155 samples from newly-diagnosed Binet A patients with clinical characteristics and outcome. FcγRIIb expression was similar in normal B-cells and leukemic cells, this being heterogenous among patients and within CLL clones. FcγRIIb expression did not correlate with well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…FcγRIIB is also expressed on cells of the innate immune system and on B cells. Bosch et al 48 reported that FcγRIIB was the only subtype of FcγR expressed on B lymphocytes and that it had potent inhibitory activity against B cells. 49 In our study, the B cell population and IgE levels declined in mice given BTL-I.…”
Section: ■ Discussionmentioning
confidence: 99%
“…FcγRIIB is also expressed on cells of the innate immune system and on B cells. Bosch et al 48 reported that FcγRIIB was the only subtype of FcγR expressed on B lymphocytes and that it had potent inhibitory activity against B cells. 49 In our study, the B cell population and IgE levels declined in mice given BTL-I.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In normal human B cells, IVIG can bind the inhibitory Fc receptor CD32B, which recruits phosphatases such as SHIP-1 to prevent BCR-mediated activation of kinase cascades [ 40 ]. CD32B is the only Fc receptor expressed by CLL cells [ 7 ]. Consistent with this, the CD32 antibody AT10 [ 37 ] partially reversed the inhibitory effects of Hizentra at 15 g/L on BCR-mediated expression of CD83 in some patients (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Большинство генов, локализованных на данных хромосомных участках, не аннотированы, и их функциональный вклад в развитие заболеваний неизвестен. Однако два гена, расположенных в хромосомном локусе 1q23.3 -FCGR2B (Fc fragment of IgG, low affi nity IIb) [13,14,15] и PBX1 (pre-B-cell leukemia homeobox 1 или пре-В-клеточный транскрипционный фактор лейкемии-1) [16,17], ассоциированы с регуляцией иммунной системы и лимфопролиферативными заболеваниями, а следовательно могут вносить вклад в развитие данной патологии. Из числа генов, расположенных в хромосомном локусе 8q24 [12], с лимфопролиферативными заболеваниями ассоциированы ген фактора, регулирующего транскрипцию -EEF1D (eukaryotic translation elongation factor 1 delta) [18], а также протоонкоген myc (bHLH transcription factor) [19,20,21]…”
Section: Discussionunclassified